Influence of recycled concrete aggregates on the flexural properties of reinforced alkali activated slag concrete. (15th January 2016) - Kathirvel, Parthiban; Kaliyaperumal, Saravana Raja Mohan
Highlights: AAS concrete can be used for sustainable structural design. Flexural properties of AAS concrete made with RCA were investigated. Compressive strength, water absorption and volume of voids were also discussed. Curing under ambient temperature may enhance its wider application in the field. Deflection and ductility properties improve with increase in the RCA content. Abstract: Alkali-activated concretes are a novel invention for substituting conventional construction materials; their main variation from conventional Portland cement concretes is utilizing comparatively alkali-rich, clinker-free binder matrix namely alkali-activated slag or geopolymer. Alkali-activated concrete is an environmental friendly and possibly considered to be a part of the sustainable development. Since, aggregates constitutes the major part of the concrete, there is a need to reduce the use of natural aggregate thereby reducing the exploitation of natural resources. This paper explains the influence of recycled concrete aggregates derived from the demolished concrete waste on the mechanical properties of geopolymer concrete (GPC). Since, very few studies been conducted using recycled aggregates in geopolymer concrete under ambient curing, an experimental work was carried out involving mixes with varying proportion of recycled aggregates and their influence on the physical, mechanical and flexural characteristics of geopolymer concrete. The results infer that the inclusion of recycled aggregate improves the strength characteristics of geopolymer concrete.